Factors affecting the decline in sea toll profits - Setiawan, Budi; Heikal, Jerry (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The Sea Toll Program represents Indonesia's strategic maritime connectivity initiative aimed at facilitating goods distribution, particularly in underdeveloped, remote, outermost, and border regions (3TP). This study examines the factors contributing to the program's declining profitability using qualitative methodology with an ethnographic approach through interviews, observations, and literature review. The research findings identify three primary factors: the high cost of replacement vessel rentals, reaching IDR 800 million per two months; port time exceeding the Department of Transportation's targets due to limited loading and unloading infrastructure; and difficulties in accessing fuel vendors in 3TP regions. These findings indicate the necessity for enhanced port infrastructure and operational efficiency to optimize the profitability of this program, which is vital for national economic equity.